ANALISIS LINGKUNGAN, KEPUASAN DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PT TELKOM INDONESIA CABANG KEDIRI - Mardika, Yoga Aldi; Kusuma Hadi Sujoko, Dodi; Muslih, Basthoumi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to analyze the significant effect of work environment, job satisfaction and workload partially or simultaneously on the performance of employees of PT Telkom Indonesia Kediri Branch. The approach used in this study is a quantitative approach and the type of causal relationship research, with the sampling technique using the Slovinn formula, the sample size in this study as many as 52 employees and the data analysis technique using descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, and hypothesis testing with SPSS Version 23 software. The results of this study are that there is a significant effect between work environment and workload on employee performance, there is no significant effect between job satisfaction on employee performance, there is a simultaneous significant effect between work environment, job satisfaction, and workload on the performance of employees of PT Telkom Indonesia Kediri Branch.